The Effect of Providing Pearl NPK Fertilizer on the Growth and Production of Sweet Corn (Zea mays saccharata Sturt) - Yoskader; Juniarny Waworuntu; Imanuel Rano Montolalu (Jurnal Penelitian Pendidikan IPA, 2023)
This research was conducted in the experimental garden of the Faculty of Agriculture, Klabat University, from August to December 2018. The research aimed to determine the response to the growth and production of sweet corn due to the application of NPK Mutiara fertilizer and to obtain the correct dose of NPK Mutiara fertilizer for the growth and production of sweet corn. This research used a Randomized Block Design (RAK) with four levels of treatment, namely T0 (without Mutiara NPK fertilizer treatment) as a control, T1 (2 gr/plant), T2 (4 gr/plant), and T3 (6 gr/plant) where each treatment was repeated four times. The research results were that the dose of Mutiara NPK fertilizer did not influence plant height and number of leaves because the growth response of sweet corn was not large enough to have a real influence on plant height and number of sweet corn leaves. The Mutiara NPK dosage influences the flowering age and cob weight because the response of the sweet corn plants is large. The dose of Mutiara NPK fertilizer does not affect plant height and number of leaves but does affect flowering time and ear weight. The best dose of Mutiara NPK fertilizer is 6 gr/plant.